Need Analysis of the Model for Writing Scientific Articles - Atmazaki; M. Zaim; Alpino Susanto; Siti Marpuah; yunisa oktavia, yunisa oktavia (International Journal of Language Pedagogy, 2024)
Students need to comprehend and become proficient in the art of writing scientific articles in order to be able to generate quality works in the form of scientific articles that they have written themselves (Matarese, 2013). Background of the research, there are problems:(1) Students have trouble coming up with ideas for scientific articles. (2) Students have trouble putting the right words together. (3) Main ideas that don't match up with the best topics. The aim of this research is need analysis of the model for writing scientific articles. The research method is both descriptive and qualitative. It involves doing preliminary research, such as a needs and context analysis, a review of the literature, and a survey of students. The people who were studied Putera Batam University students in the odd semester of 2021/2022 in state administration and english literature. The study's results show that students and teachers need the model to learn how to write scientific articles that include reading references, article reviews, observations, information and creative ideas, case studies, article manuscripts, and activated publication. The research results show that students and professors need the model to be developed based on the results of tohe needs analysis. This is because the model can help students solve their problems and get them more interested in learning by making learning fun.